How social norms contribute to physical violence among ever-partnered women in Uganda: A qualitative study - Aloysious Nnyombi; Paul Bukuluki; Samuel Besigwa; Jane Ocaya-Irama; Charity Namara; Beniamino Cislaghi (Frontiers in Sociology, 2022)
This paper contributes to the literature that studies how social norms sustain undesirable behavior. It establishes how norms contribute to intimate partner physical violence against women. First, norms organize physical violence as a domestic and private matter. Second, they organize physical violence as a constituent part of women's lives, thereby normalizing women's experience of abuse. Third, norms define appropriate boundaries within which male partners perpetrate violence. The findings draw essential information for social change interventions that target improvement in women's and girls' wellbeing. For social and behavioral programmes to change harmful norms, they have to deconstruct physical violence as a private matter, advance the de-normalization of physical violence, and dismantle acceptable boundaries within which violence happens.